Compound heterozygosity for loss‐of‐function GARS variants results in a multisystem developmental syndrome that includes severe growth retardation. Issue 10 (14th July 2017) - Oprescu, Stephanie N.; Chepa‐Lotrea, Xenia; Takase, Ryuichi; Golas, Gretchen; Markello, Thomas C.; Adams, David R.; Toro, Camilo; Gropman, Andrea L.; Hou, Ya‐Ming; Malicdan, May Christine V.; Gahl, William A.; Tifft, Cynthia J.; et al.
Abstract: Aminoacyl‐tRNA synthetases (ARSs) are ubiquitously expressed enzymes that ligate amino acids onto tRNA molecules. Genes encoding ARSs have been implicated in myriad dominant and recessive disease phenotypes. Glycyl‐tRNA synthetase (GARS) is a bifunctional ARS that charges tRNA Gly in the cytoplasm and mitochondria. GARS variants have been associated with dominant Charcot‐Marie‐Tooth disease but have not been convincingly implicated in recessive phenotypes. Here, we describe a patient from the NIH Undiagnosed Diseases Program with a multisystem, developmental phenotype. Whole‐exome sequence analysis revealed that the patient is compound heterozygous for one frameshift (p.Glu83Ilefs*6) and one missense (p.Arg310Gln) GARS variant. Using in vitro and in vivo functional studies, we show that both GARS variants cause a loss‐of‐function effect: the frameshift variant results in depleted protein levels and the missense variant reduces GARS tRNA charging activity. In support of GARS variant pathogenicity, our patient shows striking phenotypic overlap with other patients having ARS‐related recessive diseases, including features associated with variants in both cytoplasmic and mitochondrial ARSs; this observation is consistent with the essential function of GARS in both cellular locations. In summary, our clinical, genetic, and functional analyses expand the phenotypic spectrum associated with GARS variants.